PENGARUH PEMBERIAN SLUDGE PABRIK KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (ElaeisguineensisJacq.) DI PEMBIBITAN UTAMA - Rakhmad Kurniawan; Agus Sutikno; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of the research was to determine the influence of granting sludge plant oil palm to the growth of oil palm seeds and find the best treatment  for oil palm growth in main nursery. Research was carried out in land of Plant Laboratory – Agriculture Faculty University of Riau, Bina Widya Campus, Simpang Baru District KM 12.5 Pekanbaru, started from January 2014 to April 2014. This research arranged experimentaly using Completely Randomized Design (CRD),consist by 6 treatments and each treatment was repeated 4 times then obtained 24 experimental units. Each experimental unit consist of two plant seed so that the over all number of harvested seeds is 48. The treatment given was giving oil palm mill sludge, comprising: without giving sludge, sludge 500 g/​​polybag, sludge 1000 g/polybag, sludge 1500 g/polybag, sludge 2000 g/polybag and sludge 2500 g/polybag. The parameters measured were the increase of seeds height, increase amount of leaf midrib, increase of diameter hump, dry weight and root crown ratio. The statistical analysis used was tested using analysis of variance and Duncan's multiple test further at level of 5%. The results showed that giving oil palm mill sludge significant effect on seedling height increment parameter, the increase in diameter hump, seedling dry weight and the ratio of the root crown. However,no significant difference in the number of leaves on the parameters. In addition, this study showed that giving oil palm mill sludge in the treatment of 2000 g/polybag tend to give the better effecton the growth of oil palm seeds.   Keywords: Sludge, oil palm, main nursery